Numerical investigation on turbulent forced convection and heat transfer characteristic in a square channel with discrete combined V-baffle and V-orifice - Amnart Boonloi; Withada Jedsadaratanachai (My University, 2016)
Turbulent forced convection, heat transfer and performance improvement in a square channel with discrete combined baffles (DCB), which combined V-baffle and V-orifice, are investigated numerically. The influences of the flow blockage ratios (BR=0.05, 0.10 and 0.15) and V-tip directions (V-tip pointing downstream called "V-Downstream" and V-tip pointing upstream called "V-Upstream") are examined with a single pitch spacing ratio, PR=1, and attack angle, α=30o, for the Reynolds number, Re=5000–20,000. The computation results are reported in terms of flow visualizations, heat transfer characteristics, performance assessments. The results are compared with the smooth channel and the previous works. As the results, the DCB enhances the heat transfer rate and thermal efficiency due to the disturbance of the thermal boundary layer. The improvement of the heat transfer rate is around 2.8–6 times higher than the smooth channel depended on BR, V-tip directions and Re. In addition, the computational result reveals that the optimum thermal enhancement factor, TEF, is around 1.72 at BR=0.1, Re=3000 and V-Upstream.
Keywords: Baffle; Square (algebra); Forced convection; Heat Transfer Mechanisms